Can exercise affect immune function to increase susceptibility to infection? - Simpson, R. J.; Campbell, J. P.; Gleeson, M.; Krüger, K.; Nieman, D. C.; Pyne, D. B.; Turner, J. E.; Walsh, N. P. (Exercise Immunology Review, 2020)
Multiple studies in humans and animals have demonstrated the profound impact that exercise can have on the immune system. There is a general consensus that regular bouts of short-lasting (i.e. up to 45 minutes) moderate intensity exercise is beneficial for host immune defense, particularly in older adults and people with chronic diseases. In contrast, infection burden is reported to be high among high performance athletes and second only to injury for the number of training days lost during preparation for major sporting events. This has shaped the common view that arduous exercise (i.e. those activities practiced by high performance athletes/ military personnel that greatly exceed recommended physical activity guidelines) can suppress immunity and increase infection risk. However, the idea that exercise per se can suppress immunity and increase infection risk independently of the many other factors (e.g. anxiety, sleep disruption, travel, exposure, nutritional deficits, environmental extremes, etc.) experienced by these populations has recently been challenged. The purpose of this debate article was to solicit opposing arguments centered around this fundamental question in the exercise immunology field: can exercise affect immune function to increase susceptibility to infection. Issues that were contested between the debating groups include: (i) whether or not athletes are more susceptible to infection (mainly of the upper respiratory tract) than the general population; (ii) whether exercise per se is capable of altering immunity to increase infection risk independently of the multiple factors that activate shared immune pathways and are unique to the study populations involved; (iii) the usefulness of certain biomarkers and the interpretation of in vitro and in vivo data to monitor immune health in those who perform arduous exercise; and (iv) the quality of scientific evidence that has been used to substantiate claims for and against the potential negative effects of arduous exercise on immunity and infection risk. A key point of agreement between the groups is that infection susceptibility has a multifactorial underpinning. An issue that remains to be resolved is whether exercise per se is a causative factor of increased infection risk in athletes. This article should provide impetus for more empirical research to unravel the complex questions that surround this contentious issue in the field of exercise immunology.